Modern Methods of Endoscopic Diagnostics and Treatment for Upper Gastrointestinal Tract Diseases in Pediatrics - A. A. Shavrov (Jr.); A. Yu. Kharitonova; A. A. Shavrov; D. A. Morozov (Вопросы современной педиатрии, 2015)
This article presents modern methods of intraluminal endoscopic procedures for diagnostics and treatment of upper gastrointestinal diseases in pediatrics. Authors refined indications and contraindications, considered aspects of an organizational and technical equipment supply, gave clinical guidelines for application of upper gastrointestinal endoscopy methods in patients with different age groups. All that can supplement and enhance the diagnostic capabilities, as well as improve effectiveness of mini invasive endoluminal methods of treatment of esophageal, gastric and duodenal diseases in children.